Cuttings transport in horizontal and highly deviated wellbores - Mahfooz Moherei, Mazen Ahmed (2003)
Drilling horizontal and highly deviated wells is almost always accompanied by hole cleaning issues and cuttings transport problems. This study was conducted to gain more in-depth understanding of cuttings transport in this type ofwells. A flow loop was designed to address the whirling and orbital motion ofa self-eccentric drillpipe under various conditions ofhole inclinations, fluid velocity and viscosity as well as particle size. In this study, it has been observed that the orbital motion of the drillpipe plays a crucial role in the rate of cuttings-bed erosion and transport pattern under the action of streaming fluid and hence affect hole cleaning capabilities of the drilling fluid in highly deviated and horizontal sections of the well. Pipe rotation was seen to improve hole cleaning to up to 74 %. Annular velocity and degree of turbulence is also shown to be critical for efficient hole cleaning requirements. Increasing hole inclination from 60° to 90° has a substantial effect on hole cleaning, in most situations a 28% improvement was established as the angle turns from 60° to 90°. However, the effect of increasing fluid viscosity at velocities ofthis study adversely affect hole cleaning. Increasing the system kinematic viscosity from 1 cSt to 10 cSt turns the system from turbulent to laminar flow and resulted in about 38 % reduction in hole cleaning. Finally cuttings size was found to have a minor effect on hole cleaning. In this study, cuttings of 1.2 and 2.4 mm were used. Higher velocities and pipe rotation as well as higher viscosities and hole inclination seemed to assist transportation of large particles than smaller ones.